Development of A Tourist Destination Object Search Application as A Madura Tourism Information Media Using ADDIE Model - Fatah, Doni Abdul; Suzanti, Ika Oktavia; Ifandia, Alfian Mahendra; Negara, Yudha Dwi Putra; Mufarroha, Fifin Ayu (Universitas Bina Darma, 2024)
The rapid development of tourism has caused many tourists to be interested in enjoying it. Madura Island is a small archipelago and is part of East Java. Madura consists of 4 districts, namely Bangkalan district, Sampang district, Pamekasan district, and Sumenep district. With the number of districts owned, it creates a diversity of tourism. The development of the tourism sector must also be accompanied by the development of information technology. Utilization of technology can improve accommodation in supporting tourist destination services by designing an android-based application for searching for objects supporting Madura tourism destinations. The purpose of this research is to create an object search application that supports tourist destinations and serves as a medium for information about tourist locations on the island of Madura, making it more straightforward for tourists/users to enjoy their vacation. The stages of research carried out using ADDIE Model include knowing the system requirements, analysis and design, Development, implementation, and Evaluation. The results of the study are in the form of applications by detecting supporting objects including places of interest, gas stations, lodging, religion, culinary and health. It is expected that users when visiting Madura tourism will be easy, fun, and can enjoy their holidays.